On Obtaining The First Impact Response Of Split Hopkinson Pressure Bar Apparatus - Zulkifli, Amirul Amri Mohd (Universiti Sains Malaysia, 2017)
Split Hopkinson Pressure bar (SHPB), also referred as Kolsky bar is commonly used setup for high strain rate testing. SHPB is suitable for high strain rate test for safety and structural integrity assessment of structures subjected to dynamic loading. A sample is sandwiched between two bars and compress after impact from striker bar that propelled via gas gun. During testing using SHPB apparatus, a multiple impact on sample is exist. The multiple impact came from disturbance wave inside the bar of the SHPB that effect failure behavior of the sample. The aim of this study is to design, fabricate, and commission a momentum trap suitable for SHPB apparatus and to obtain the first impact response of it in the form of impulsive pulse. The momentum trap were set up in front of the existing SHPB before test. The test were done with comparison the behavior of voltage (v) vs time (s) graph that used to indicated impact behavior of the apparatus. A comparison of incident pulse in voltage graph are made before and after using the momentum trap. Finally, the result show that the multiple impact can be avoid by using the momentum trap.